Shariah Bank in Facing the Global Financial Crises: A Historical Comparative toward Efficiency and Productivity of Shariah Bank in Global Financial Crises - aqida shohiha (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Purposes: The article aims to describe in compartive view of how the shariah bank faces the global financial crises. Both effinciency and productivity is selected as main variabel to understand the main issues.Design/Methodology/Approach: Quantitative with explonatory design, namely DEA, is applied in this research. In practise, various hyphoteses was tested through empirical data.Findings: It can be proved that, there are significance different in effienciency and productivity of shariah bank before and after global crises of finance. To sum up, efficiency of shariah bank decrease extremely after crises. But, conversely, their productivity indicate an increasing in various indicators. In general, in both efficiency and productivity of shariah bank shown a rebalancing in two aspects. With level 99,23% point. Originality/Value: This study contribute new information for that crises can effect significantly to efficiency and productivity of financial industries such as shariah bank.